Perancangan Dual-Band Antena Mimo 1x4 Untuk 5G Smartphone - Fitria, Lisma; Rahayu, Yusnita; Kurniawan, Adit (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The last decade has been enormous invasion of wireless device in the evolution of technology. The requirement of high throughput is needed to provide the quality of device such as audio, data, video, and games. However, the connected devices grown and increase critcially year by year. Multiple Input Multiple Output (MIMO) that embedded for 4G technologies as one of technology that more likely to adapted on 5G to improve the data peak rate for SNR (Signal-to-Noise Ratio). Multiple Input Multiple Output (MIMO) confirmed that can be the solution to provide better efficiency. This paper will proposed the design of dual band MIMO antenna 1x4 for 5G smartphone. The proposed antenna is designed RT Duroid 5880 substrate with overall dimension size of 150x70mm. The antenna consist of 8 elements that achieved -25.24 dB of return loss at 28 GHz frequency while at 38 GHz is -26.84 dB. Then achieved gain 8.82 dBi at 38 GHz frequency and 9.52 dBi at 38 GHz. Keyword: MIMO, 5G,Dual-band, Smarthphone, Microstrip.